EFFECTIVENESS OF A WHEELCHAIR SKILLS TRAINING IN PATIENTS WITH TRAUMATIC SPINAL CORD INJURY - Ляховецкая, Вера Витальевна; Васильченко, Елена Михайловна; Коновалова, Нина Геннадьевна (Medicine in Kuzbass, 2018)
Disabled persons cannot master modern rehabilitation assistive devices independently and need a training.Study objective – to evaluate the effectiveness of the wheelchair skills training in patients with traumatic spinal cord injury.Materials and methods. One hundred and fifty-six patients with traumatic spinal cord injury and disability group 1 were observed during the wheelchair skills training process. Examination of before and after the training course included assessment of patients’ wheelchair use skills by their performance of a battery of tests that were compiled on the basis of WHEELCHAIR SKILLS TEST. Training course was run within routine rehabilitation treatment and included 10 thirty-minutes individual lessons: demonstration of tutorial videos, performance of the exercises by instructor, performance of the exercises by patients at first with assistance and then independently.Results. All patients became more mobile and mastered maneuvers that increase their independence and assure safety when moving around in a wheelchair. Specific training results depended on the level of spinal cord injury, severity of neurological deficit and initial skills of a patient.Discussion. The severity of a neurological deficit defines the ability to master and implement a wide range of capabilities provided by modern wheelchairs. High safety level when using a wheelchair is assured in all patients despite the spinal cord injury level or the severity of neurological deficit.Conclusion. Disabled persons with traumatic spinal cord injury and the 1 group of disability need a training course to develop skills for effective and safe use of a wheelchair.
Keywords: wheelchair; traumatic spinal cord injury; patients; training